The shortest periodic and flaring flux variability of a methanol maser emission at 6.7 GHz in G 014.23−00.50. (24th May 2017) - Sugiyama, Koichiro; Nagase, Katsura; Yonekura, Yoshinori; Momose, Munetake; Yasui, Yasutaka; Saito, Yu; Motogi, Kazuhito; Honma, Mareki; Hachisuka, Kazuya; Matsumoto, Naoko; Uchiyama, Mizuho; Fujisawa, Kenta
Abstract: We detected flaring flux variability that regularly occurred with a period of 23.9 d on a 6.7 GHz methanol maser emission at V lsr  = 25.30 km s −1 in G 014.23−00.50 through highly frequent monitoring using the Hitachi 32 m radio telescope. Analyzing data from 2013 January 5 to 2016 January 21, the periodic variability has persisted in at least 47 cycles, corresponding to ∼1100 d. The period of 23.9 d is the shortest one observed in masers around high-mass young stellar objects so far. The flaring component normally falls below the detection limit (3 σ) of ∼0.9 Jy. In the flaring periods, the component rises above the detection limit with a ratio of the peak flux density more than 180 in comparison with the quiescent phase, showing intermittent periodic variability. The timescale of the flux rise was typically two days or shorter, and both symmetric and asymmetric profiles of flux variability were observed through intraday monitoring. These characteristics might be explained by a change in the flux of seed photons in a colliding-wind binary (CWB) system, or a variation of the dust temperature by the extra heating source of a shock formed by a CWB system within a gap region in a circumbinary disk, in which the orbital semi-major axes of the binary are 0.26–0.34 au.